Recruiting a PRA Team That Works - Kohl, Jon; Candanedo, Indra (My University, 1997)
In 1949 the world bank sent 14 international advisers to Colombia. These expert in foreign exchange, transportation, industry, agriculture, and others represented the first mission of its kind to attack "underdevelopment" with a comprenhensive program calling for intervention in all social and economic aspects of importance (Escobar 1995).
In 1949 the world bank sent 14 international advisers to Colombia. These expert in foreign exchange, transportation, industry, agriculture, and others represented the first mission of its kind to attack "underdevelopment" with a comprenhensive program calling for intervention in all social and economic aspects of importance (Escobar 1995).